Formal Verification for WiMAX Networks Using Enhanced Security Protocols - Afrizal Zein; Lubis, Julianto (Journal of Science Technology (JoSTec), 2023)
This study discusses the formal verification of the Worldwide Interoperability for Microwave Access (WiMAX) security protocol. WiMAX security specifications are defined as a security property that must be met by the protocol in a WiMAX network. The security properties that must be met include pseudonymity, information confidentiality, anti-tapping and session key secrecy. Several studies have found several failures to comply with the security properties set by the WiMAX IEEE 802.16-2004 and IEEE 802.16e-2005 standards. Some of the attacks that can occur include jamming, scrambling, DoS attacks, replay attacks, modification of management messages, downgrade attacks, interleaving attacks and other types of security attacks. From some of these attacks there are several solutions to improve security protocols to overcome these attacks so that they can comply with security protocols. Proof of security protocols in the ability to fulfill security properties can be done either formally or informally. The security protocol operational semantic model framework developed by Cas Cremers and Sjouke Mauw is used to carry out formal verification of proposed improvements to the authentication protocol and Privacy and Key Management (PKM) protocol. Modeling the proposed protocol with an operational semantic framework has been able to prove the proposed improvement of the authentication protocol and PKM by using timestamps, SS/BS identity encryption and adding digital signatures or message digest values ​​to ensure authentication is able to meet the specified security properties.